Schwann Cell Precursors; Multipotent Glial Cells in Embryonic Nerves - Jessen, Kristjan R.; Mirsky, Rhona (Frontiers in Molecular Neuroscience, 2019)
The cells of the neural crest, often referred to as neural crest stem cells, give rise to a number of sub-lineages, one of which is Schwann cells, the glial cells of peripheral nerves. Crest cells transform to adult Schwann cells through the generation of two well defined intermediate stages, the Schwann cell precursors (SCP) in early embryonic nerves, and immature Schwann cells (iSch) in late embryonic and perinatal nerves. SCP are formed when neural crest cells enter nascent nerves and form intimate relationships with axons, a diagnostic feature of glial cells. This involves large-scale changes in gene expression, including the activation of established glial cell markers. Like early glia in the CNS, radial glia, SCP retain developmental multipotency and contribute to other crest-derived lineages during embryonic development. SCP, as well as closely related cells termed boundary cap cells, and later stages of the Schwann cell lineage have all been implicated as the tumor initiating cell in NF1 associated neurofibromas. iSch are formed from SCP in a process that involves the appearance of additional differentiation markers, autocrine survival circuits, cellular elongation, a formation of endoneurial connective tissue and basal lamina. Finally, in peri- and post-natal nerves, iSch are reversibly induced by axon-associated signals to form the myelin and non-myelin Schwann cells of adult nerves. This review article discusses early Schwann cell development in detail and describes a large number of molecular signaling systems that control glial development in embryonic nerves.